Disability and Loneliness: A Critical Study of Males under British Social Policies - Guo, Shuheng (International Journal of Social Sciences and Public Administration, 2024)
Loneliness, which is a subjective perception of an individual’s feelings about social relationships, is a public health problem that can easily be overlooked, especially in the disabled population. The complexity of loneliness deserves to be analysed in depth when gender factors and disability co-exist. Employing a case study approach, this paper explores social policy options for loneliness among adult disabled men in the UK from an Evidence for Policy and Practice perspective, taking full account of the unique sensitivities of this group. Based on the theoretical framework of socio-ecological models and the policy cycle, the study critically discusses three cases of social policy evidence in recent years, identifying the strengths and limitations of different policies. Finally, this paper offers some recommendations for addressing the policy problem of loneliness among males with disabilities from the perspective of social policymakers, creating a more inclusive and supportive social environment.